Otimização do tracionamento de canino impactado pela técnica do arco segmentado: relato de caso clinico - Maia, Luiz Guilherme Martins; Maia, Mila Leite de Moraes; Machado, André Wilson; Monini, André da Costa; Gandini Júnior, Luiz Gonzaga [UNESP] (My University, 2010)
Upper canines impaction are considered the second most frequent and are associated to important esthetics and functional limitations. Among the treatment strategies described in the literature the most commonly used are the extraction of the primary canines and the surgical exposure followed by orthodontic traction, that requires an adequate interdisciplinary approach. The aim of this case report is to draw the attention of the clinician to the possibility of adapting the segmented arch technique to manage a canine impaction clinical case.

A impacção de caninos superiores permanentes tem sido apontada como a segunda rnais frequente, criando problemas estéticos e funcionais de grande relevância. Diversas estratégias de tratamento são citadas na literatura, variando desde a exodontia dos caninos deciduos até a exposição cirúrgica seguida de tracionamento ortodôntico, o que requer uma abordagem interdisciplinar. O objetivo do presente artigo é esciarecer aspectos importantes acerca da impacção de caninos superiores e ressaltar a possibilidade do tratamento por meio do tracionamento ortodôntico utilizando a técnica do arco segmentado.
Impacted canine treatment through orthodontic traction using segmented arch technique: case report
Keywords: Teeth - impaction; Teeth abnormalities; Dentition (tooth development); Cuspids; Dental therapeutics; Ooperative dentistry; Caninos; Dente impactado; Má oclusão; Ortodontia